2008
DOI: 10.1007/s11027-008-9166-1
|View full text |Cite
|
Sign up to set email alerts
|

The rains are disappointing us: dynamic vulnerability and adaptation to multiple stressors in the Afram Plains, Ghana

Abstract: Adaptation, Afram plains, Africa, Agriculture, Community, Ghana, Food security, Water, Vulnerability,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 45 publications
0
58
0
Order By: Relevance
“…These constraints also hamper their ability to cope with changing environmental conditions (Downing et al 1997;Westerhoff and Smit 2009). Community-based studies have provided insights into the various stresses that affect people and their livelihoods.…”
Section: Climate Change Impacts Vulnerability and Adaptation (Iva)mentioning
confidence: 99%
See 2 more Smart Citations
“…These constraints also hamper their ability to cope with changing environmental conditions (Downing et al 1997;Westerhoff and Smit 2009). Community-based studies have provided insights into the various stresses that affect people and their livelihoods.…”
Section: Climate Change Impacts Vulnerability and Adaptation (Iva)mentioning
confidence: 99%
“…Farmers are already noticing changes in rainfall and in seasonality (Casale et al 2010;Laube et al 2012;Tambo and Abdoulaye 2013). They are experiencing unpredictability in the onset of the rainy season (Assan and Kumar 2009;Laube et al 2012), increased incidences of drought (Hesselberg and Yaro 2006;Westerhoff and Smit 2009), and more intense rainfall, sometimes leading to increased flooding (Westerhoff and Smit 2009;Casale et al 2010;Tschakert et al 2010). These biophysical drivers act to deplete people's natural capital by shortening the growing season and decreasing soil moisture and soil fertility (Quaye 2008;Batisani 2012;Milgroom and Giller 2013).…”
Section: Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet a community's exposure-sensitivity and adaptive capacity to climate change cannot be understood independently of the various other forces which affect the community and to which it adapts. The effects of changing climate conditions are felt synergistically with the effects of changing economic, political, social, cultural and technological conditions (Adger and Kelly 1999;Kasperson and Kasperson 2001;Turner et al 2003;FĂŒssel and Klein 2006;Tschakert 2007;Westerhoff and Smit 2008). Research on practical climate adaptation has shown that adaptations are rarely to climate change alone (hence "double exposure" and "multiple exposure"), and adaptations are invariably undertaken as part of ongoing risk management, resource management, or development strategies (hence "mainstreaming") Thomalla et al 2005;Belliveau et al 2006).…”
Section: Vulnerability Concepts and Frameworkmentioning
confidence: 99%
“…Important factors include: a) the demographic and socioeconomic characteristics of populations and their available assets; b) the capacity of populations to foresee, resist, react to, recover from, cope with, and take advantage of hazards and stresses; and c) the way in which governance and policies (e.g., infrastructure provision, health and education) influence those characteristics and adaptive capacities (Romero-Lankao and Qin 2011). To a much greater extent, this perspective showcases the role of non-climatic socioeconomic factors (O'Brien et al 2004;Reid and Vogel 2006;Tschakert 2007;Westerhoff and Smit 2009;Ziervogel and Taylor 2008). Reducing contextual vulnerability, therefore, emphasizes existing vulnerabilities and reducing them through addressing the underlying processes and factors that determine exposure, sensitivity, and most importantly, adaptive capacity (Schipper 2007;Boyd et al 2009;Jones and Boyd 2011).…”
mentioning
confidence: 99%